The Relationship Between Husband's Support and Anxiety Levels Experienced by Pregnant Women at the Independent Midwifery Practice (BPM) of Lilis Suriani Tampubolon - Ferika Desi; KhoirunnisaBatubara; Ester Selfia Napitupulu (Cattleya Darmaya Fortuna, 2026)
Pregnancy is a period accompanied by physical and psychological changes that can trigger anxiety in expectant mothers, particularly during the second and third trimesters. Husband support is one factor that plays a role in reducing anxiety. This study aimed to analyze the relationship between husband support and anxiety levels among pregnant women at the Lilis Suriani Tampubolon Independent Midwifery Practice (BPM) in Gunung Tua Lumban Pasir Village, Panyabungan District, Mandailing Natal Regency. The study employed a quantitative design with a correlational approach. The sample consisted of 50 pregnant women selected via random sampling. The instruments used were a husband support questionnaire and the Beck Anxiety Inventory (BAI). Data analysis was conducted using univariate and bivariate methods, specifically the Chi-Square test. The results showed that the majority of respondents received husband support categorized as